You need to evaluate the following limit such that:

`lim_(x->-oo) (-2x + 8) /(sqrt(x^2+x)) = oo/oo`

You may force factor x to numerator such that:

`lim_(x->-oo) x(-2 + 8/x)/(sqrt(x^2+x))`

You may force factor `x^2` to denominator such that:

`lim_(x->-oo) x(-2 + 8/x)/(sqrt(x^2(1+x/x^2)))`

You should remember that `sqrt(x^2) = |x|` and...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to evaluate the following limit such that:

`lim_(x->-oo) (-2x + 8) /(sqrt(x^2+x)) = oo/oo`

You may force factor x to numerator such that:

`lim_(x->-oo) x(-2 + 8/x)/(sqrt(x^2+x))`

You may force factor `x^2` to denominator such that:

`lim_(x->-oo) x(-2 + 8/x)/(sqrt(x^2(1+x/x^2)))`

You should remember that `sqrt(x^2) = |x|` and since `x->-oo ` `=> |x| = -x` such that:

`lim_(x->-oo) x(-2 + 8/x)/(-xsqrt(1+1/x))`

Reducing x yields:

`lim_(x->-oo) (-2 + 8/x)/(-sqrt(1+1/x)) = (-2 + lim_(x->-oo) (8/x))/(-sqrt(1 + lim_(x->-oo) (1/x)))`

`lim_(x->-oo) (-2 + 8/x)/(-sqrt(1+1/x)) = (-2 + 0)/(-sqrt(1+0))`

`lim_(x->-oo) (-2 + 8/x)/(-sqrt(1+1/x)) = (-2)/(-1) = 2`

**Hence, evaluating the given limit yields `lim_(x->-oo) (-2x + 8) /(sqrt(x^2+x)) = 2.` **